Distribution of Atmospheric Aerosol over the South China Sea - Shih-Jen Huang; Chen-Chih Lin (Advances in Meteorology)
The satellite-derived aerosol optical depth (AOD) data is used to investigate the distribution of aerosol over the South China Sea (SCS). High correlation coefficients are found between in situ AERONET data and satellite AOD measurements around the SCS with the highest coefficient of 0.9 on the Dongsha Island (i.e., Pratas Island). The empirical orthogonal function (EOF) analysis of AOD over the SCS shows that high AOD is always found around offshore areas of China, Indochina, Sumatra, and Borneo. Besides, spring is the major season of occurring coarse aerosol particles (AOT_C) but fine aerosol particles (AOT_F) occur yearly. The biomass burning is found in Indochina during March and April, and so it is in Sumatra and Borneo from August to October. The results also show that the AOT_F are higher during El Niño events, but higher AOT_C are found in La Niña years.